2017
DOI: 10.1016/j.schres.2016.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Cortical thickness of neural substrates supporting cognitive empathy in individuals with schizophrenia

Abstract: Background Cognitive empathy is supported by the inferior frontal gyrus (IFG), anterior mid-cingulate cortex (aMCC), insula (INS), supplementary motor area (SMA), medial prefrontal cortex (mPFC), right temporo-parietal junction (TPJ), and precuneus (PREC). In healthy controls, cortical thickness in these regions has been linked to cognitive empathy. As cognitive empathy is impaired in schizophrenia, we examined whether reduced cortical thickness in these regions was associated with poorer cognitive empathy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 67 publications
6
17
0
Order By: Relevance
“…However, in terms of ranking importance, functional connectivity information showed slightly superior performance than structural information, and with regard to structural information, cortical information was superior to subcortical information in classification performance. Taken together, it appears that aberrant functional connectivity and structural abnormalities in the cortex should be given more weight, which is in line with recent research findings (Dong et al, 2017 ; Larivière et al, 2017 ; Massey et al, 2017 ; Mørch-Johnsen et al, 2017 ; Peters et al, 2017 ).…”
Section: Discussionsupporting
confidence: 85%
“…However, in terms of ranking importance, functional connectivity information showed slightly superior performance than structural information, and with regard to structural information, cortical information was superior to subcortical information in classification performance. Taken together, it appears that aberrant functional connectivity and structural abnormalities in the cortex should be given more weight, which is in line with recent research findings (Dong et al, 2017 ; Larivière et al, 2017 ; Massey et al, 2017 ; Mørch-Johnsen et al, 2017 ; Peters et al, 2017 ).…”
Section: Discussionsupporting
confidence: 85%
“…In recent years brain lesion and imaging studies have been widely used to explore the neural mechanisms that underlie empathy. Research has shown that cognitive empathy is generally supported by the activation of the medial prefrontal cortex (MPFC), right temporoparietal junction (TPJ), inferior frontal gyrus (IFG), supplementary motor area and anterior midcingulate cortex (aMCC; Völlm et al, 2006 ; Schulte-Rüther et al, 2007 , 2008 ; Hooker et al, 2008 , 2010 ; Massey et al, 2017 ) while emotional empathy involves the activation of brain regions such as the IFC, anterior insula (INS), anterior cingulate cortex (ACC) and superior temporal sulci (STS; Schulte-Rüther et al, 2008 ; Shamay-Tsoory et al, 2009 ; Shamay-Tsoory, 2011 ; Leigh et al, 2013 ; Oishi et al, 2015 ). Shamay-Tsoory et al ( 2009 ) found that patients who have suffered damage to the ventral MPFC experience low levels of cognitive empathy and that those who have sustained damage to the IFC exhibit low levels of emotional empathy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, magnetic resonance imaging (MRI) studies of the neural mechanisms underlying empathy are extensive. Massey et al ( 2017 ) found that the cortical thickness of the mPFC, right IFG, aMCC, INS and left TPJ in healthy subjects is significantly associated with cognitive empathy. Pfeifer et al ( 2008 ) found the significant activation of the right IFG, right INS and right amygdala in children during engagement in empathic behavior and showed that the activation of the right IFG is significantly associated with the Interpersonal Reactivity Index (IRI), a self-reported empathy questionnaire.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations